A Personal Narrative on Learning English and the Influence of Sociocultural Theories - Siusana Kweldju; Dyah Fitri Mulati; Dian Puspa Negara; Andy Mappewali; Sahyoni; Suhono, Suhono (Anglophile Journal, 2024)
This autoethnographic study explores my personal journey of learning English, framed through the lens of sociocultural theory. By reflecting on key stages of my life, from early childhood exposure and formal schooling to informal learning through media and peer interaction, the research describes how language development is not a linear or purely academic process, but one shaped by social relationships, cultural environments, and evolving identity. Drawing on Vygotsky’s sociocultural theory and related scholarship, the narrative traces how various mediators, including family, teachers, technology, and community have influenced my motivation, confidence, and sense of belonging in English-speaking contexts. The findings reveal that language learning is deeply intertwined with identity negotiation and cultural integration, culminating in a sense of ownership over the English language. This study contributes to the field by emphasizing the emotional, reflective, and personal dimensions of language acquisition, which are often overlooked in traditional second language research. It suggests that incorporating learners’ lived experiences, informal learning practices, and identity development into language education can foster more inclusive and meaningful pedagogies. The research also opens pathways for further studies using narrative and qualitative approaches to better understand the complex, socioculturally embedded nature of language learning.